How are social bonds to a romantic partner related to criminal offending - Nielsen, Alva Albæk (European journal of criminology, 2018)
This study uses a combination of Danish administrative register and survey data on a representative sample aged 18–64 (N = 11,114) to investigate the importance of social bonds to a romantic partner. Results show that people with strong social bonds to their romantic partner offend significantly less than people with weak social bonds to their partner. The study finds no difference in offending between people with weak social bonds to their partner and people without a partner. Additionally, one result shows that strong social bonds matter less for the risk of offending if a person is aged over 30; however, this result is mainly suggestive.